We must be brave [compact disc, unabridged] : a novel - Liardet, Frances (Penguin Audio, 2019)
December 1940. In the disorderly evacuation of Southampton, England, newly married Ellen Parr finds a small child asleep on the backseat of an empty bus. No one knows who little Pamela is. Ellen professed not to want children with her older husband, and when she takes Pamela into her home and rapidly into her heart, she discovers that this is true: Ellen doesn't want children. She wants only Pamela.